The level of food insecurity prevalence in Universitas Sultan Ageng Tirtayasa (Untirta) Banten AMID Covid-19 - Nani Maryani; Fitria Hasanah; Dwi Ratnasari; Eva Johan (UHAMKA PRESS, 2021)
Disease pandemic has a dramatic impact on global socio-economic, such as the current COVID-19 pandemic. Global food insecurity prevalence has increased as the impact of the pandemic and Indonesia is not an exception. In this research, we assessed food insecurity prevalence among civitas academics of Untirta, Banten. We used 8-items of Food Insecurity Experiencing Scale (FIES) that is globally used by FAO to measure food insecurity in many countries. The data was analyzed using Rash Model approach with free open access software R. A number of 12,8% of the respondents was categorized as moderate food insecurity and 3,8% was severe food insecurity. Among three groups of civitas academics, the students were the most vulnerable group to moderate food insecurity, the lecturers were the most secure group, and the staffs were the most diverse group from secure to severe food insecurity. There was no correlation between food insecurity with social demographic factors such as gender, age, and education background. Students who experience moderate food insecurity should be given an intervention by the university and government to address this issue as students is our hope for better future of the nation. This research gives insight into food security among civitas academics in light of COVID-19 pandemic.